PROBLEMATIKA PEMBENTUKAN KARAKTER DI LEMBAGA PENDIDIKAN DAYAH - M. Arif Idris; Suroto (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2021)
Dayah is an educational institution that leads to an informal educational process. The existence of Dayah in the midst of a pluralistic society consisting of various races and religions certainly has its own problems in character building. The purpose of this study is to see how the problems of character building in dayah educational institutions in Aceh are. This type of field research (field research) with a qualitative descriptive research approach. Collecting data through interviews, study documentation, and observation. The results of the study indicate that the problems of dayah education in shaping the character of students in Aceh Singkil, Simeuleu, and Sabang districts are different. There are at least three problems faced by dayah in character building, namely 1) science and technology, 2) parental support, and 3) readiness of dayah educational institutions.